2016
DOI: 10.1083/jcb.201510098
|View full text |Cite
|
Sign up to set email alerts
|

Doa1 targets ubiquitinated substrates for mitochondria-associated degradation

Abstract: Mitochondria-associated degradation (MAD) mediated by the Cdc48 complex and proteasome degrades ubiquitinated mitochondrial outer-membrane proteins. MAD is critical for mitochondrial proteostasis, but it remains poorly characterized. We identified several mitochondrial Cdc48 substrates and developed a genetic screen assay to uncover regulators of the Cdc48-dependent MAD pathway. Surprisingly, we identified Doa1, a substrate-processing factor of Cdc48 that inhibits the degradation of some Cdc48 substrates, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(124 citation statements)
references
References 88 publications
3
121
0
Order By: Relevance
“…While our paper was under revision, another group published results confirming our observations concerning the ubiquitination of Mdm34 by Rsp5 and the role of the PY motif in this post-translational modification 55 . However, in their experimental conditions, Wu et al.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…While our paper was under revision, another group published results confirming our observations concerning the ubiquitination of Mdm34 by Rsp5 and the role of the PY motif in this post-translational modification 55 . However, in their experimental conditions, Wu et al.…”
Section: Resultssupporting
confidence: 71%
“…However, in their experimental conditions, Wu et al. observe very high levels of Mdm34 polyubiquitination (polyubiquitinated chains >170 kDa), which are implicated in the rapid turnover of the protein 55 . Their results do not conflict with those presented here but they indicate that the length of ubiquitin chains may change the fate of Mdm34.…”
Section: Resultssupporting
confidence: 69%
“…A similar model has also been proposed for the role of p97 in mitophagy, where p97‐mediated extraction of factors on the outer membrane, such as mitofusins, is thought to facilitate the clearance of damaged mitochondria or mitophagy (Tanaka et al , ; Chan et al , ). Of note, extraction of mitofusins involves the Ufd1‐Npl4 cofactor (Kim et al , ; Wu et al , ), whereas we identified a distinct set of cofactors in lysophagy including the DUB, YOD1. DUBs such as YOD1 were also shown to contribute to extraction of proteins from the ER membrane during ER‐associated degradation (Ernst et al , ; Liu & Ye, ; Stein et al , ).…”
Section: Discussionmentioning
confidence: 62%
“…To explore the molecular basis for p97 activity in lysophagy, we aimed to identify the relevant cofactors that cooperate with p97 in the process. We speculated that the lysosomal damage response involves the p97 cofactors UBXD1 and PLAA, because they had previously been linked to the endolysosomal system or autophagy in different systems and are affected by p97 disease mutations (Ren et al , ; Ossareh‐Nazari et al , ; Ritz et al , ; Wu et al , ). Moreover, we considered the DUB, YOD1, whose homologue OTU1 physically and genetically interacts with p97 and PLAA/Ufd3 in yeast (Rumpf & Jentsch, ).…”
Section: Resultsmentioning
confidence: 99%
“…Data information: In this figure, GFP-Pex15D30 was expressed from a centromeric plasmid under the control of TEF1 promoter, and WT and mutant forms of Msp1-FLAG were expressed from the endogenous chromosomal locus. Msp1 E193Q -FLAG ( Fig 1D, lanes [5][6][7][8][9][10][11][12][13][14][15]. Therefore, most of the residues are required for substrate binding.…”
Section: Resultsmentioning
confidence: 99%